Stafne's Defect with Buccal Cortical Expansion: A Case Report - Paulo Sérgio Flores Campos; José Aloysio Carvalho Oliveira; Janaina Araújo Dantas; Daniela Pita de Melo; Nilson Pena; Luís Antônio Nogueira Santos; Iêda Margarida Rocha Crusoé-Rebello (International Journal of Dentistry)
A rare case of Stafne's bone cavity, type III-G, is reported in a 49-year-old male patient who had been referred to a private clinic for a routine evaluation. The final diagnosis was based on computed tomography. Scintigraphy played a fundamental role in determining the most likely etiology.